Scoping Review on the Use of Drugs Targeting JAK/STAT Pathway in Atopic Dermatitis, Vitiligo, and Alopecia Areata - Ana M. Montilla; Francisco Gómez-García; Pedro J. Gómez-Arias; Jesús Gay-Mimbrera; Jorge Hernández-Parada; Beatriz Isla-Tejera; Juan Ruano (Adis, Springer Healthcare, 2019)
Abstract Introduction The JAK/STAT signaling pathway is involved in the immune-mediated inflammatory skin diseases atopic dermatitis (AD), vitiligo, and alopecia areata (AA), and represents a potential target when developing treatments. So far, no drugs targeting this pathway have been approved for the treatment of dermatological diseases. We reviewed the use of drugs blocking the JAK/STAT pathway in the aforementioned diseases. Methods An a priori protocol was published. We used Joanna Briggs Institute Reviewer's Manual methodology to conduct the review and PRISMA Extension for Scoping Review (PRISMA-ScR) to report results. MEDLINE, EMBASE, CINAHL, Scopus, and Web of Science databases were searched in a three-step approach on April 2019 by two researchers. Results Ninety-six mainly multicenter observational studies were included (66, 10, and 20 studies on AA, vitiligo, and AD, respectively). Tofacitinib and ruxolitinib were mainly used for the three diseases, and also upadacitinib, abrocitinib, baricitinib, cerdulatinib, delgocitinib, gusacitinib for AD, and baricitinib, PF-06700841, and PF-06651600 for AA. All patients with AD improved, whereas patients with vitiligo and patients with AA showed varied responses, including unresponsive cases. The safety profiles were similar for all drugs and diseases, mainly comprising mild or no adverse events. Conclusions Evidence on the efficacy and safety of drugs targeting the JAK/STAT pathway for the treatment of patients with AD, vitiligo, or AA is increasing but is still of low quality.